Flavor-Related Quality Attributes of Ripe Tomatoes Are Not Significantly Affected Under Two Common Household Conditions - Kanski, Larissa; Naumann, Marcel; Pawelzik, Elke (Frontiers in Plant Science, 2020)
Consumer complaints about the flavor of fresh tomato fruits (Solanum lycopersicum L.) have increased in the past few decades, and numerous studies have been done on the flavor of tomatoes and how it is influenced. However, it has not yet been taken into account how consumer handling affects the flavor when considering the complete post-harvest chain—from retailer (distributor) to retail to consumer. In this study, the impact of two household storage regimes on the volatile profile and important flavor-related compounds were examined, considering the entire post-harvest handling. New breeding lines (n = 2) and their parental cultivars (n = 3) were evaluated. Fruits were harvested ripe and stored at 12.5°C for one day, at 20°C for two days, and afterward at either 20°C or 7°C for another four days. The aroma volatile profile was measured using GC-MS and GC-FID. A trained panel was used to characterize the sensory attributes of the fruits. In both storage regimes, the relative amount of hexanal increased during the storage period in three of the five cultivars/breeding lines while benzaldehyde was the only volatile compound that decreased significantly in four cultivars/breeding lines. The relative concentration of the precursors of lipid-derived volatiles—linoleic (C18:2) and linolenic (C18:3) acid—did not change in both storage regimes. The lycopene and ß-carotene contents increased slightly during storage (20°C and 7°C), as the carotenoid-derived volatile 6-methyl-5-hepten-2-one did. The fructose and glucose concentrations did not vary significantly, while the content of total soluble solids increased during both storage regimes. No significant difference could be found between the fruits stored at 20°C or 7°C for four days after the post-harvest handling in all the parameters analyzed, including the sensory analysis, considering all cultivars/breeding lines. A storage temperature of 7°C is not detrimental for the flavor of ripe fruits under the experimental conditions used. The genetic background of the studied cultivars/breeding lines have a higher impact on the flavor variation than the two common household storage conditions when storing ripe fruits and taking the entire post-harvest handling into account.